A dynamic generalized fuzzy multi-criteria croup decision making approach for green supplier segmentation. - Do Anh Duc; Luu Huu Van; Vincent F Yu; Shuo-Yan Chou; Ngo Van Hien; Ngo The Chi; Dinh Van Toan; Luu Quoc Dat (PLoS ONE, 2021)
Supplier selection and segmentation are crucial tasks of companies in order to reduce costs and increase the competitiveness of their goods. To handle uncertainty and dynamicity in the supplier segmentation problem, this research thus proposes a new dynamic generalized fuzzy multi-criteria group decision making (MCGDM) approach from the aspects of capability and willingness and with respect to environmental issues. The proposed approach defines the aggregated ratings of alternatives, the aggregated weights of criteria, and the weighted ratings by using generalized fuzzy numbers with the effect of time weight. Next, we determine the ranking order of alternatives via a popular centroid-index ranking approach. Finally, two case studies demonstrate the efficiency of the proposed dynamic approach. The applications show that the proposed appoach is effective in solving the MCGDM in vague environment.